2010
DOI: 10.1002/we.427
|View full text |Cite
|
Sign up to set email alerts
|

A review on scale and siting of wind farms in China

Abstract: Using a wind power information system, which is based on the geographic information system (GIS), this paper presents a statistical analysis of built and approved wind farms to the end of 2008. The average capacity of wind turbine generators (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Wind speed density and wind direction for a given terrain play a significant role in maximizing power capture. With advanced manufacturing technologies and the availability of automation, the production costs for a wind turbine have lowered in the past decade [13]. Apart from the wind resource, complex terrains add a significant problem to the turbine siting process where the irregular land and scanty resources increase transportation and labor cost significantly.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Wind speed density and wind direction for a given terrain play a significant role in maximizing power capture. With advanced manufacturing technologies and the availability of automation, the production costs for a wind turbine have lowered in the past decade [13]. Apart from the wind resource, complex terrains add a significant problem to the turbine siting process where the irregular land and scanty resources increase transportation and labor cost significantly.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The method utilised historical data from existing wind farms and the aim of the study was to predict power as a decision factor for future investment of a wind farm. A review of the scale and siting of wind farms in China was undertaken by Deng et al (2011). They found that the average capacity of wind farms is increasing and complex terrain can limit the size of wind farms due to increased costs.…”
Section: Introductionmentioning
confidence: 99%
“…Proximity of urban areas, transportation infrastructure and slope were also frequently incorporated in past suitability analyses. A recent review of wind farms in China indicates the practice of placing wind turbines in sparsely vegetated and populated areas, as well as on land with low slopes . Mann et al .…”
Section: Introductionmentioning
confidence: 99%